Characteristics, utilisation and influence of viewpoint articles from the Structured Operational Research and Training Initiative (SORT IT) – 2009-2020 [version 1; peer review: 2 approved] - Mohammed Khogali (F1000Research, 2021)
Background: The Structured Operational Research and Training Initiative (SORT IT) teaches the practical skills of conducting and publishing operational research (OR) to influence health policy and/or practice. In addition to original research articles, viewpoint articles are also produced and published as secondary outputs of SORT IT courses. We assessed the characteristics, use and influence of viewpoint articles derived from all SORT IT courses. Methods: This was a cross-sectional study involving all published viewpoint articles derived from the SORT IT courses held from August 2009 - March 2020. Characteristics of these papers were sourced from the papers themselves and from SORT-IT members involved in writing the papers. Data on use were sourced from the metrics provided on the online publishing platforms and from Google Scholar. Influence on policy and practice was self-assessed by the authors of the papers and was performed only for papers deemed to be ‘calls for action’. Results: A total of 41 viewpoint papers were published. Of these, 15 (37%) were ‘calls for action’. In total, 31 (76%) were published in open-access journals and the remaining 10 in delayed access journals. In 12 (29%) of the papers, first authors were from low and middle-income countries (LMICs). Female authors (54%) were included in 22, but only four (10%) and two (5%) of first and last authors respectively, were female. Only seven (17%) papers had available data regarding online views and downloads. The median citation score for the papers was four (IQR 1-9). Of the 15 ‘call for action’ papers, six influenced OR capacity building, two influenced policy and practice, and three influenced both OR capacity building within SORT IT and policy and practice. Conclusion: Viewpoint articles generated during SORT IT courses appear to complement original OR studies and are valued contributors to the dissemination of OR practices in LMICs.